(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Fibre reinforced polymer (FRP) composites still give designers the ability to deliver innovativeand intelligent solutions to beat the ever growing aging problems in the infrastructure. Since it’s been over50 years since the introduction of FRP materials to the development business, this paper presents a progressivereview of historic and up-to-datedevelopments of FRP in strengthening and rehabilitation engineeringapplications. This review highlights a fewof the classic and modern experimental, numerical, and analyticalstudies related to the mixing of FRPs into buildings, among different structures. The discussion representedherein aims at covering the application of FRP systems in concrete structural members and conjointly highlightsthe performance of FRPs (including bonding agents) beneath extreme conditions like elevated temperature,saline atmosphere, and cycles of physical change and thawing. This paper conjointly presents a collective perspective onseveral limitations, challenges, and analysis desires related to flourishing, property, and sturdy implementation of FRPs in civil infrastructure.